Scolytinae species damaging Carya illinoinensis trees in southern Brazil - Poletto, Tales; Corrêa Costa, Ervandil; do Nascimento Machado, Dayanna; Maus da Silva, Jéssica; Régis Perini, Clérison; Brião Muniz, Marlove Fátima (Revista Ceres, 2025)
This study aims to report two species of Scolytinae that have been damaging Carya illinoinensis trees in southern Brazil. In two Brazilian municipalities, Guarapuava in Paraná State and Pantano Grande in the Rio Grande do Sul State, insects of the Scolytinae family were found damaging pecan trees. Infested tree samples were kept in the laboratory in glass tubes sealed with a voile tissue until the emergence of adults. After the adults’ emergence, the specimens were identified by their morphological characteristics and sent to a taxonomist specialized in Scolytinae family for identification. The species Xyleborus retusus was identified causing damages to pecan trees from Guarapuava while the species Xyleborus ferrugineus was identified in pecan trees from Pantano Grande. Trees injured by these insects displayed similar symptoms in both study areas. In Guarapuava and Pantano Grande, 13 and 10 trees, respectively, died due to stem lesions caused by Xyleborus spp. Thus, this study reports for Brazilian pecan growers the occurrence of Scolytinae species X. retusus and X. ferrugineus damaging C. illinoinensis plants in southern Brazil. It also emphasizes the importance of constant crop monitoring to minimize the risk of pest damage.